(untitled) (El-Wahat Journal for Research and Studies, 2026)
This study aimed to highlight the impact of AI-powered digital advertising and social influencers on consumer behavior in the digital environment. This topic is of great importance in light of the developments in technology and information enabled by the internet, which have made the world a small global village and transformed ordinary citizens into digital citizens. It has also led to a series of changes in the media and communication, which in turn contributed to the production and reproduction of a new conceptual arsenal such as electronic advertising, artificial intelligence, and social influencers. These concepts have affected consumer behavior in the virtual environment, Electronic advertising is considered one of the most important pillars of public and private institutions in the field of marketing, promoting their services and products, benefiting from the advantages of artificial intelligence applications and the popularity of social influencers on social media sites, so it has become a symbolic capital for institutions within the virtual space.